Decolorization of direct red and direct blue dyes used in handmade paper making by ozonation treatment. Issue 8 (13th February 2016) - Agarwal, Saakshy; Sharma, Ashwini; Singh, Kailash; Gupta, A.B.
Abstract: Handmade paper utilizes direct dyes for imparting it bright colors to be used in wedding cards, fancy, decorative arts, etc. The effluent of handmade paper industry faces problem of highly colored effluent. The present study aims at decolorization of direct red and direct blue dyes, used abundantly in the industry, with the help of ozonation treatment. The batch studies have been conducted on decolourization of synthetic samples of these dyes at various initial concentrations, temperature, and pH. The effect of these parameters has been studied on decolorization efficiency. The maximum decolorization is achieved at pH of 10 and temperature of 313 K. The equilibrium time of decolorization with ozonation treatment for direct red and direct blue dye for 50 ppm initial concentration was 6 and 4 min, respectively. The kinetics of decolorization was found to be pseudo-first-order type.